A Correction For The Latent Period Of Chemically Coupled Neurons - O. A. Dunaeva (Моделирование и анализ информационных систем)
We consider the estimation of the spike delay induced by external sinaptic influence. We propose a first-order estimation for the latent period of synapse coupled spiking neurons.